Honesty and integrity in the KOE, IIUM - Kabbashi, Nassereldeen Ahmed (IIUM Press, 2011)
The universities and education face great challenges, most of them indirectly or directly related to science. Academic honesty and integrity are fundamental values in a community of scholars. The student shares with the faculty the responsibility for maintaining the integrity of scholarship, grades, and professional standards, therefore students at university develop habits that help them to survive. It is necessary for scholars to think and work as a student, and resume the methods developed during undergraduate days. Scholars at the Kulliyyah of Engineering (KOE) International Islamic University (IIUM), must satisfactory engage in learning with their students and in various forms of community service and industry liaison, in addition to attend several meetings per semesters. Those pressures can attempt people to take short-cut that do not meet KOE community standards for honesty and integrity. At the KOE incidents of student cheating are very low but the cases start to increase. This paper tries to highlight the reason behind why honesty and integrity among scholars break down and why cases of cheating among students increased as well.